2014
DOI: 10.3906/tar-1403-83
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early cropping on vegetative development, productivity, and fruit quality of Gala and Braeburn apple trees

Abstract: The effects of 5 crop load levels (all fruit removed and 10, 20, 30, and 40 fruit per tree) in the second growing year on vegetative growth, productivity, and fruit quality were studied in apple cultivars Gala and Braeburn on M9 rootstock in the second and the third leaf. An increase in vegetative growth was observed on the defruited trees in the second growing year. The highest crop load of 40 fruits per tree reduced average fruit weight by 18.7% in Gala compared to those obtained on the trees carrying the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
2
13
0
1
Order By: Relevance
“…No significant differences for total soluble solids (TSS) and total acidity (TA) in cvs. Gala and Braeburn apples were found as related to crop load (Radivojević et al, 2014), which is similar to our study. In cv.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…No significant differences for total soluble solids (TSS) and total acidity (TA) in cvs. Gala and Braeburn apples were found as related to crop load (Radivojević et al, 2014), which is similar to our study. In cv.…”
Section: Resultssupporting
confidence: 81%
“…Crop load significantly affected fruit weight in apple cv. Braeburn as the fruits with diameter of less than 70 mm were only found on the trees carrying the heaviest crop (Radivojević et al 2014). In FBT + FT, there was no significant difference in total number of fruits in trees thinned with 10 and 15 μl·l -1 NAA, but average fruit weight was lower at 15 μl•l-1 (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Crop loads 4.1, 6.0, and 7.8 reached and/or exceeded 50 MT/ha (Table 1) in 2017, making them potential targets for management strategies. Radivojevic et al [43] concluded that both "Braeburn" and "Gala" could be loaded up to 13 fruits/cm 2 TCSA in their third growing season to achieve this 50 MT/ha goal. This crop load is clearly much higher than what was assessed here, and what is demonstrated throughout literature.…”
Section: Crop Load Effect On Yield and Fruit Sizementioning
confidence: 99%
“…In addition, morphological characteristics sometimes have correlation or are associated with characteristics that are difficult to evaluate such as disease susceptibility. Therefore, they may be useful as markers in breeding programs (Karimi et al 2009;Koc and Bilgener 2013;Radivojevic et al 2014).…”
Section: Introductionmentioning
confidence: 98%